Targeted Therapy in Hepatocellular Carcinoma - Clarinda W. L. Chua; Su Pin Choo (International Journal of Hepatology)
Hepatocellular carcinoma (HCC) is one of the commonest cancers worldwide, as well as a common cause of cancer-related death. HCC frequently occurs in the setting of a diseased cirrhotic liver and many patients present at an advanced stage of disease. Together with a poor functional status, this often precludes the use of systemic therapy, especially conventional cytotoxic drugs. Moreover, HCC is known to be a relatively chemo-refractory tumor. There have been many targeted drugs that have shown potential in the treatment of HCC. Many clinical trials have been carried out with many more in progress. They include trials evaluating a single targeted therapy alone, two or more targeted therapy in tandem or a combination of targeted therapy and conventional chemotherapy. In this article, we seek to review some of the more important trials examining the use of targeted therapy in HCC and to look into what the future holds in terms of targeted treatment of HCC.